Should a third party know your research submission to institutional ethics committee a dilemma? - Amit Kumar C Jain (Medicine Science, 2021)
Research studies are now a part of every student and teachers in a medical college and their aim can range from completion of thesis to need for promotion. Irrespective of the purpose, studies, especially prospective types done on human or animals often require approval from institutional ethics committee and its considered today to be mandatory. However during the course of submission of research proposal, is it right for others to know your research? This article throws a highlight on this dilemma. [Med-Science 2021; 10(2.000): 662-3]